Perancangan dan Pengembangan Aplikasi Untuk Kegiatan Santri di Pesantren Menggunakan Metode Agile - Dodi Siregar; Sarudin (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Santri activities in Islamic boarding schools must have several things in an activity such as technical activities, activity groups, and a list of activity events. Data collection on activities at Islamic boarding schools, especially at the Mawaridussalam Islamic Boarding School, is still manual, using stationery and not neatly structured, such as in data collection on licensing activities at the Education Department office. Making a list of activities and dividing groups into each activity, resulting in difficulties when sharing data to other fields. The application of student activities in Islamic boarding schools using the Agile method is a research objective to reduce problems that occur in the Care Department and to make activity data collection easier, as well as becoming information that can be accessed by anyone using electronic devices in the form of PCs/Laptops and smartphones. So this application for student activities in Islamic boarding schools becomes an application that can make data collection easier with features for filling in, editing and deleting data, as well as managing existing data into new data in licensing activities. Enter data on students in the activity groups provided and make a list of activities for one period with columns in accordance with the standards in the Islamic boarding school